Economic Growth, Climate Change and Clean Energy in a Post- COVID Era - Osabohien, Romanus; Jaaffar, Amar Hisham; Setiawan, Doddy; Igharo, Amechi E. (International Journal of Energy Economics and Policy, 2025)
This study analyzes how clean technology, including electric vehicles, clean cooking and lighting fuels, renewable energy, and renewable electricity generation, might assist to reduce climate change and promote sustainable development. These goals include improving health and well-being (SDG-3), ensuring clean water and sanitation (SDG-6), promoting industry, innovation, and infrastructure (SDG-9), combating climate change (SDG-13), developing sustainable cities and communities (SDG-11), protecting life below water (SDG-14), and preserving life on land (SDG-15). The study employed data from the World Development Indicators (WDI) and the Generalized Method of Moments (GMM). According to the research, the deployment of clean energy technology has the ability to drastically lessen the impact of climate change, ensuring the long-term survival of the environment and ecosystems on a worldwide scale. The move from gasoline-powered vehicles to electric vehicles propelled by renewable energy sources has the potential to considerably cut carbon emissions related with transportation. Furthermore, installing energy-efficient appliances and lighting can efficiently minimize energy consumption and the carbon footprint connected with home power usage.